Developmental seizures and mortality result from reducing GABAA receptor α2-subunit interaction with collybistin - Rochelle M. Hines (Nature Portfolio, 2018)
The inhibitory synaptic protein collybistin (CB) and GABAAR-α subunits are thought to interact, but strength and specificity are unclear. Here the authors study the CB–α2 interaction and show that a mouse mutated in the CB-binding region of α2 displays a loss of specific synapses and seizure.